Applications of Polymethylhydrosiloxane (PMHS) in Organic Synthesis- Covering up to March 2022 - Mujahid Alam, Mohammed; Seema, Vittal; Dubasi, Narsimhaswamy; Kurra, Mohan; Varala, Ravi (Mini-Reviews in Organic Chemistry, 2023)
Based on the type of metal or non-metal catalyst used, the authors of this paper have clearly highlighted the different applications of air-stable, commercially viable, and environmentally friendly polymethylhydrosiloxane (PMHS) in organic synthesis or other allied reactions. The importance of PMHS was emphasised for the particular organic transformation's success. In addition to its wellknown use as a reducing agent, it has also been demonstrated in a variety of other applications, including ring cleavage, the cotton industry, functional material for microfluidic chips, and the dehydroaromatization of bio-oils. The article tries to compile the most noteworthy cases of highly successful PMHS catalysis over the past two decades or so.
Keywords: organic synthesis